Update on the classification of vasculitis. - Waller, R; Ahmed, A; Patel, I; Luqmani, R (2013)
Classification criteria have an important role and practical use in everyday rheumatology. Improvement in therapy and our understanding of the aetiopathogenesis of vasculitis have driven the need to have better descriptors and groupings of diseases. This in turn will allow newer therapy and further understanding to have a greater impact. The American College of Rheumatology (ACR) classification criteria have been an important advance but have limitations. There remains confusion between classification and diagnostic criteria and definitions. We hope to resolve this using evidence-based improvements in classification and diagnostic criteria. Further understanding of the underlying causative mechanisms could lead to diagnostic testing, eliminating the need for classification criteria.